Gentle Touch and Sucrose for Pain Relief during Suctioning in Preterm Newborns-A Randomized Clinical Trial - Nayara Rodrigues Gomes de Oliveira; Cibelle Kayenne Martins Roberto Formiga; Bruna Abreu Ramos; Rafaela Noleto dos Santos; Nayara Nubia de Sousa Moreira; Patricia Gonçalves Evangelista Marçal; Waldemar Naves do Amaral (MDPI AG, 2023)
Pain management is challenging in neonatal care. We aimed to compare the effects of gentle touch and sucrose on pain relief during suctioning in premature newborns (PTNB). This crossover randomized clinical trial enrolled PTNBs with low birth weight, hemodynamically stable, and requiring suctioning during hospitalization in the neonatal intensive care unit. PTNBs underwent three different suctioning procedures. The first was performed without intervention (baseline). Right after, PTNBs were randomly allocated (sucrose and gentle touch or vice versa) to the next two suctioning procedures. Two validated scales assessed pain: the Neonatal Infant Pain Scale (NIPS) and the Premature Infant Pain Profile-Revised (PIPP-R). We evaluated 50 PTNBs (mean of 28 weeks) with a mean low birth weight of 1050 g; most were under continuous positive airway pressure 37 (74%) and mechanical ventilation 41 (82%). Gentle touch was efficacious for pain relief since NIPS (p = 0.010) compared to baseline. Sucrose was also effective in reducing pain NIPS and PIPP-R (p < 0.001). Although the two interventions reduced pain, no difference was observed between gentle touch and sucrose.